1970
DOI: 10.1530/jrf.0.0230033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Age on Ovulation, Corpora Lutea of Pregnancy, and Implantation Failure in Mice

Abstract: Summary. C57B1 female mice aged 4 to 7 months (controls) and 8 to 9, 10 to 11, 12 to 13, and 14 to 15 months were mated and killed at 12 hr, 60 hr or 7\ m=1/ 2\ days post coitum (p.c.). Corpora lutea were counted and evaluated in serially sectioned ovaries. Implantation sites were counted in the animals killed 7\ m=1/ 2\ days p.c. The mean number of implantations in 10-to 11-month-old mice was less than in the control animals. This decrease was closely associated with morphological degeneration of corpora lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 15 publications
5
29
0
Order By: Relevance
“…These data are in agreement with previous investigations that have shown no decrease in ovulation rate until middle age (200-280 days old) in NCS mice [17]. It was also reported that there was no significant difference in ovulation rate between young (4-7 months) and old (10-13 months) mice [1,10]. However, it appeared that ovulation rates in NCS mice decreased, markedly between the ages of 300 and 330 days.…”
Section: Discussionsupporting
confidence: 93%
“…These data are in agreement with previous investigations that have shown no decrease in ovulation rate until middle age (200-280 days old) in NCS mice [17]. It was also reported that there was no significant difference in ovulation rate between young (4-7 months) and old (10-13 months) mice [1,10]. However, it appeared that ovulation rates in NCS mice decreased, markedly between the ages of 300 and 330 days.…”
Section: Discussionsupporting
confidence: 93%
“…Ovarian reserve, determined by AMH levels, is correlated with litter size in dogs (Hollinshead et al 2016), which could have large consequences for cumulative, lifetime reproductive fitness. In some strains of mice and cows, low ovarian reserve or reproductive ageing is associated with reduced corpus luteum function (Harman & Talbert 1970, JimenezKrassel et al 2009). In these cases, the mechanism of infertility may relate to a reduced ability to maintain pregnancy (Mossa et al 2012, Martinez et al 2016, rather than production of low-quality oocytes.…”
Section: The Effect Of Ovarian Reserve On Declining Fertilitymentioning
confidence: 99%
“…Progesterone was found to have a significant effect but the oestrogen effect was not significant. (Harman & Talbert, 1970), although such changes could be a result of pregnancy loss (Talbert, 1971), and the histological assessment of luteal function is not reliable (Finn, 1970 (Finn, 1963) or by giving orthotopic ovarian grafts from young mice (Krohn, 1966). Measurements of plasma progestins in the hamster (Blaha, 1971) and in the rabbit (Spilman, Larson, Concannon & Foote, 1972) have shown that hormone levels are similar in young and old animals, except when there were no viable fetuses late in pregnancy (Spilman et al, 1972), and supplementary progesterone and oestrogen did not increase embryonic survival in old rabbits (Larson, Spilman, Dunn & Foote, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…This reduced fertility of old mice cannot be attributed to a decline in ovulation rate since the number of CL of pregnancy remain high (Biggers, Finn & McLaren, 1962;Harman & Talbert, 1970). Embryonic losses caused by failure of fertilization and preimplantation development in ageing CBA/H-T6 mice appear to be small (Gosden, 1973a), suggesting that most of the prenatal mortality occurs at or soon after the time of implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation